Pengembangan Kualitas Diri Pemimpin: Suatu TinjaunTeologis Menurut 1 Timotius 4: 12-13 - Tonny Andrian Stefanus; Herling Fredriek Bulahari; Napoleon Manalu (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2022)
Leadership begins with a spritual personal ability possessed, demonstrated through roles and functions, manifested in a moral form that can inspire the lives of others. This means that leadership that can generate trust for others is not only built by authority or spiritual factors solely in an office and power but by exemplary. Talking about leadership in the context of believers is certainly closely related to the moral responsibility that is possessed. This is not only the standard in building one's identity as a spiritual human being that first needs to be achieved and can build, awaken the people around him. The development of self-quality becomes a pattern that strategically improves leadership abilities that have testimony in a wider scope and scope. On the one hand, leadership that can improve self-quality will move dynamically both internally and externally. This can happen because of the benefits caused, penetrating space and time according to the capacity possessed.